Nation in translation: the South Slavic mythomoteurs in the early modern period - Blažević, Zrinka (2011)
The South Slavic cultural sphere has always been a liminal zone of cultural hybridizations and syncretisms. They have been determined by fluctuating and asymmetrical constellations of the political, social, economic and symbolic powers, making a kind of network within which cultural forms are selected, transferred and modified. Seen from that perspective, cultural transfers in the South Slavic cultural zone could be conceptualized as a kind of delocalized translational practice, i.e. an interactive process of complex inter- and trans-cultural negotiations within various translational scenarios. In addition to this, it must be stressed that transcultural activity has simultaneously been realized on the two levels: vertically, in terms of creative transfers of European cultural models in the regional cultural domain, and horizontally, as an interactive exchange of cultural patterns between various local (ethno)cultural groups. For that reason, the South Slavic cultural identities should not be considered as fixed and homeostatic categories, but as processual phenomena which have been constantly (re)producing themselves in the liminal field of the translational. In this paper the complex features and modalities of multilayered and multidirectional cultural translations and transfers within the South Slavic region will be illustrated by comparative analysis of auto- and hetero- images which were constitutive elements of the most influential early modern Croatian and Serbian mythomoteurs. These points will be exemplified on the works of two authors: first, on historiographical opus of Croatian polymath Pavao Ritter Vitezovic (1652-1713) who was both discursive creator of the exclusivist Croatian (proto)national ideology and the author of the first history of the Serbs (Serbiae illustratae libri octo), and second, on two chronicles (Romanian chronicle and Slavo-Serbian chronicles) of Serbian historian Djorde Brankovic (1665-1711), who fused indigenous Serbian Orthodox historical tradition with the analogous Western models in order to make his national narrative transculturally legible. Paradoxically, although both of thes early modern mythomoteurs displayed manifold structural similarities, they formed an ideological axis of exclusivist Croatian and Serbian 19th-century national-integrational ideologies. As a theoretical and methodological foundation for this kind of research historical and critical discourse analysis will be employed, while a topical analysis wil be used as a research procedure for the multidimensional process of intertextual, interdiscursive and intermedial circulation of the auto- and hetero-images. This analysis will clearly demonstrate how every cultural translation inevitably results in a kind of ideological hybridization and subversion of the reductive nationally exclusivist models.